Nanopartículas no controle da mancha bacteriana do tomateiro e no tratamento de sementes - Milan, Mariany Dalila (2024)
Bacterioses are responsible for major losses in tomato cultivation, among the pathogens species of the genus Xanthomonas spp. are responsible for causing bacterial spot on tomatoes, the main bacteriosis of the crop. The objectives of this study were to evaluate the use of nanoparticles (Nps) of ZnO, ZnOCl, Ag2O, ZnO: Ag, ZnO: Cu, ZnO: K, ZnO: Mg, ZnOCl: Ag and ZnOCl: Cu in the control of bacterial spot on tomatoes caused by X. vesicatoria, X. euvesicatoria pv. euvesicatoria, X. euvesicatoria pv. perforans and in seed treatment. The toxicity of NPs in inhibiting bacterial growth in vitro, preventive and curative application on tomato plants, as well as seed treatment in inhibiting detection and its effect on germination were evaluated. NPs of Ag2O, ZnO: 0.3Ag, ZnO: 7Ag, ZnO: 9Ag, ZnOCl: 10Ag, ZnO: 10K inhibited the in vitro bacterial growth of X. vesicatoria, X. euvesicatoria pv. euvesicatoria, X. euvesicatoria pv. perforans. The ZnO: 5K, ZnO: 0.1Cu and ZnOCl: 0.1Cu NPs reduced the number of CFU of the three bacterial species over time. Preventive application of ZnO: 0.1Cu at [1.5] and ZnO: 5K at [2.5] and curative application of ZnO: 5K [1.5 and 2.5] and ZnO: 0.1Cu at [2.5] have reduced the progress of the disease caused by X. euvesicatoria pv. perforans. As for the species X. euvesicatoria pv. euvesicatoria, the preventive application of ZnO: 0.1Cu [2.5] and ZnO: 5K [1.5 and 2.5], as well as the curative application ZnO: 5K [1.5 and 2.5], ZnOCl: 0.1Cu [1.5 and 2.5] and ZnO: 0.1Cu [1.5 and 2.5] have significantly reduced the progress of the disease. Preventive application of ZnOCl: 0.1Cu [2.5] and ZnO: 0.1Cu [1.5 and 2.5] and curative application of ZnO: 5K [1.5 and 2.5], ZnOCl: 0.1Cu [2.5] and ZnO: 0.1Cu [1.5 and 2.5] have been more effective at controlling Xanthomonas vesicatoria than copper hydroxide. Seeds treated with ZnO showed a lower percentage of detection of X. euvesicatoria pv. perforans. Seeds treated with ZnO, ZnO: 0.1Cu, ZnOCl and ZnOCl: 0.1Cu efficiently reduced the detection of X. euvesicatoria pv. euvesicatoria. None of the NPs have reduced the detection of X. vesicatoria. Tomato seeds inoculated and treated with ZnOCl, ZnOCl: 0.1Cu showed similar results to copper hydroxide, improving seed germination.